Cosmological simulations of the circumgalactic medium with 1 kpc resolution: enhanced H i column densities - Voort, Freeke van de; Springel, Volker; Pakmor, Rüdiger (Monthly notices of the Royal Astronomical Society. Letters, 2019)
ABSTRACT. The circumgalactic medium (CGM), i.e. the gaseous haloes around galaxies, is both the reservoir of gas that fuels galaxy growth and the repository of
Advance access publication 2018 October 10
Gesehen am 06.02.2019